The Effect of Financial Stress on the Composite Stock Price Index (IHSG) - Afrilianto; Animah; Tri Hanani (SIMAK, 2026)
This study is motivated by the increasing instability of the global economy, which impacts the Indonesian financial market, particularly through financial stress that affects the movement of the Composite Stock Price Index (IHSG). The aim of this study is to analyze the influence of the Financial Stress Index (FSI) on the IHSG in Indonesia. The research method used is a quantitative approach with multiple linear regression analysis based on monthly data over a specific period. The results indicate that the FSI has a significant effect on the movement of the IHSG, reflecting that financial stress has a spillover effect on the domestic stock market. These findings highlight the importance of financial stability policies to minimize the impact of financial stress on the Indonesian capital market.